Distinctly different temporal trends exist between neonatal and paediatric home enteral tube feeding (HETF) in the same UK region. (24th May 2012) - Paxton, CE; Wade, K; Ardill, R; Lee, HM; Eyles, L; Freer, Y; Menon, G; Wilson, DC
Abstract : Background: HETF is increasingly being used to provide nutrition support (NS) for children but differences in the extent of use and temporal usage trends in neonatal compared to paediatric clinical practice are unreported. Aims: To determine: 1. Absolute numbers of children and neonates discharged on HETF from the tertiary paediatric and neonatal units in the same region, and trends in the same over an extended period. 2. The numbers of neonates transferred on tube feeding from regional neonatal to regional paediatric unit over the last 2 years of the time period and their outcome. Methods: A retrospective cohort study (database and clinical note review) to compare numbers of children discharged on HETF from the single regional neonatal unit and single regional paediatric unit serving a UK population of 838, 573, and their inter-relationships. All children and neonates discharged on HETF over the study period 01.07.00-30.06.11 were included. Results: 485 children were discharged on HETF from the regional paediatric hospital compared with 114 from the neonatal unit over the same time period. Over the study period a rise in numbers discharged on HETF from the paediatric unit was observed (average of 34 per year in 2000-2005 increasing to 55 per year in 2006-2011), however there was a decreasing number discharged from the neonatal unit (average of 16 per year in 2000-2005 decreasing to 8 per year in 2006-2011). HETF was primarily used short term in the neonatal group for immaturity alone. During the 2-year period of the study 07/09-06/11, 20 neonates were transferred to the regional paediatric unit on ETF. Eleven (55%) of these were subsequently discharged on HETF from the paediatric unit, but these neonatal transfers only accounted for 10% of the 103 paediatric discharges on HETF. Conclusions: These novel data demonstrate that the incidence of HETF usage on discharge from a UK paediatric regional centre continues to increase whilst that from the neonatal unit serving the same region is falling, and that sick neonates transferred on ETF make up only a small number of incident paediatric HETF cases.